2018
DOI: 10.1177/1073858418755352
|View full text |Cite
|
Sign up to set email alerts
|

Neural Oscillations Orchestrate Multisensory Processing

Abstract: At any given moment, we receive input through our different sensory systems, and this information needs to be processed and integrated. Multisensory processing requires the coordinated activity of distinct cortical areas. Key mechanisms implicated in these processes include local neural oscillations and functional connectivity between distant cortical areas. Evidence is now emerging that neural oscillations in distinct frequency bands reflect different mechanisms of multisensory processing. Moreover, studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
121
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 103 publications
10
121
2
Order By: Relevance
“…There are a number of ways in which these proposed roles of alpha oscillations could mediate visual–vestibular interactions: firstly as a gating mechanism to integrate modality‐specific inputs arriving from distant neural areas. This fits with the idea that coherence of oscillatory neural signals is critical for multisensory perception (Keil & Senkowski, ; Senkowski, Schneider, Foxe, & Engel, ). Secondly, alpha oscillations could reflect the inhibition of movement in the visual field due to self‐motion, in line with a general role for alpha‐band oscillations in suppression and selection of attention and the ability to be consciously oriented in time and space (Klimesch, ).…”
Section: Introductionsupporting
confidence: 88%
“…There are a number of ways in which these proposed roles of alpha oscillations could mediate visual–vestibular interactions: firstly as a gating mechanism to integrate modality‐specific inputs arriving from distant neural areas. This fits with the idea that coherence of oscillatory neural signals is critical for multisensory perception (Keil & Senkowski, ; Senkowski, Schneider, Foxe, & Engel, ). Secondly, alpha oscillations could reflect the inhibition of movement in the visual field due to self‐motion, in line with a general role for alpha‐band oscillations in suppression and selection of attention and the ability to be consciously oriented in time and space (Klimesch, ).…”
Section: Introductionsupporting
confidence: 88%
“…The different sensory channels provide complementary information, the integration of 3 which leads to more accurate and faster behavioral decision (Welch and Warren, 1980;Stein and 4 Meredith, 1993). The neural basis of multisensory integration and its loci in the hierarchy of brain 5 computations have been the focus of myriad of studies (see for reviews (Talsma et al, 2010;ten 6 Oever et al, 2016;Keil and Senkowski, 2018)). It is now well established that multisensory 7 integration starts early in the process chain Schroeder and Foxe, 8 2005): both animal and human studies have demonstrated that the genesis of multisensory 9 integration relies on cross-modal inputs to sensory cortices which informs about the 10 spatiotemporal co-occurrence of sensory cues (Bizley et al, 2007;Lakatos et al, 2007;Kayser 11 et al, 2008;Cappe et al, 2010;Mercier et al, 2013Mercier et al, , 2015Atilgan et al, 2018).…”
mentioning
confidence: 99%
“…In other words, the fact that there was only enhancement but no suppression effect might be due to a flooring effect and/or inherent hard connectivity between sensory cortices. Our findings also critically implicate the role of the neural oscillations and effective connectivity, especially in the alpha frequency range [25], subserving multisensory processing [2].…”
Section: Discussionmentioning
confidence: 72%
“…We continuously encounter with visual and auditory information, processed by distinct sensory cortices, which are eventually integrated to produce a conscious behavioral unique response [1, 2]. However, when visual and auditory information is incongruent or in conflict, one sensory modality may dominate the other, leading towards a multisensory illusion [3].…”
Section: Introductionmentioning
confidence: 99%